2019
DOI: 10.1002/ldr.3289
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial succession and dynamics of soil fungal communities in restored grassland on the Loess Plateau in China

Abstract: Natural secondary succession of degraded soil has improved the ecological environment of the Loess Plateau, profoundly influencing the succession and dynamics of soil fungal communities restored grasslands in particular. This chronosequence and the varied topography of the Loess Plateau thus provide a unique opportunity to synchronously investigate the variation of soil quality and fungal communities as they develop over time and space. Here, we used high-throughput sequencing of the ITS rRNA gene region to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 88 publications
(94 reference statements)
4
18
0
Order By: Relevance
“…The temporal dynamics of soil microbial communities are usually investigated in chronosequences of land restoration in natural conditions (Lauber et al 2013 ; Liu et al 2019 ) and different developmental stages of crop plants root microbiota (Zhang et al 2018 ). A vital indicator for the dynamics of microbial succession is the temporal turnover of the time–decay relationships, which have been used to describe decreasing community similarities over time (Nekola and White 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The temporal dynamics of soil microbial communities are usually investigated in chronosequences of land restoration in natural conditions (Lauber et al 2013 ; Liu et al 2019 ) and different developmental stages of crop plants root microbiota (Zhang et al 2018 ). A vital indicator for the dynamics of microbial succession is the temporal turnover of the time–decay relationships, which have been used to describe decreasing community similarities over time (Nekola and White 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, according to the actual situation of the Songnen Plain, a lot of degraded grassland or abandoned farmland has been converted to reseeding grassland via natural succession. In fact, the vegetation restoration changes environment condition, by directly modifying root systems, and the exudates as well indirectly affecting soil quality and even soil microbes 20,21 . Concurrently, some studies have suggested that plant succession could significantly alter the structure of SMC and have a large-scale effect on soil carbon and nitrogen content 22,23 .…”
mentioning
confidence: 99%
“…Kruskal-Wallis nonparametric testing ("agricolae" package) was used to distinguish significant differences among groups. Gephi was used for the network analysis, and the parameters (Liu et al, 2019) and genera with low abundances (<0.001%) were eliminated from each group (De et al, 2018). All correlations in the operational taxonomic unit (OTU) abundance were used to create a network in which each node represents one OTU, and each edge represents the correlation between the nodes and significant correlations between the nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research of the relationship between keystone species and environmental factors (Liu et al, 2019), the introduction of BL decreases the forest habitat humidity and enhances the fungal community. As a fast-growing tree, BL also uses nutrients (Duan et al, 2017).…”
Section: Co-occurrence Network Of Black Locust and Native Plantsmentioning
confidence: 99%